Clinico-morphological evaluation of Hypertrophic Cardiomyopathy patients in cardiac MRI with an evaluation of prognostic parameters in tertiary cardiac centre (Journal of Invasive and Clinical Cardiology, 2025)
Background: Cardiac Magnetic Resonance Imaging (MRI) has several advantages over 2D Echocardiography (Echo) for the diagnosis, management, and prognostication of Hypertrophic cardiomyopathy (HCM). The efficacy of which is less studied in our part of the world. Thus, this study aims to evaluate, clinical and morphological characteristics involving Echo and cardiac MRI along with the comparison of morphological features and determination of morphological prognostic factors of HCM from MRI.Methods: This is a prospective, cross-sectional study conducted in SGNHC and Bir Hospital Kathmandu, Nepal. This Study included 73 patients fulfilling inclusion criteria from 20th May 2023 to 19th May 2024.Results: Out of 73 patients, with a clinical diagnosis of the HCM, 59 (80.8%) were males and 14 (19.2%) were females. Statistically significant differences (P